Determinación de los niveles de glicemia en pobladores adultos de ambos sexos, atendidos en el puesto de salud de Buenos Aires sur del distrito de Víctor Larco, en agosto del 2013 - Cruz Flores, Melisa Isabel (2016)
This fieldwork aimed to determine blood sugar levels in adult people of both sexes treated at the Health Post "Buenos Aires Sur" - Victor Larco Herrera district, August 2013, a total of 65 samples were processed serum in adult volunteers of both sexes. With respect to the population studied, a total percentage of glucose analysis 23.77% from 69.23% in men and in women was presented. In the biochemical analysis of blood glucose, samples of volunteers with hypoglycemia, low normal range in both men and women was 13.8%, these results would be giving evidence that patients could be manifesting pathological conditions such conditions are observed hepatic, Addison disease, hypothyroidism, etc; in a normal range of blood glucose spanned the 58.46% of the processed sample and 27.6% of the samples showed hyperglycemia. Percentages obtained for hyperglycemic values, 15.3% were female patients and 12.3% for male patients. This hyperglycaemia may be due to excessive production and release of glucose into blood by the liver with a decrease in glucose utilization by the tissues and the resistance of insulin to the quantities of glucagon or other patients could be occurring type II diabetes